TEACHING KNOWLEDGE OF THE CHINESE NATIONAL ORCHESTRA AT THE SICHUAN CONSERVATORY OF MUSIC IN CHINA - Wu, Tengteng; Woramitmaitree, Narongruch (International Online Journal of Education and Teaching, 2023)
The article provides an overview of the history, reputation, and instruments of the orchestra, which can help readers understand the unique features and cultural significance of this traditional Chinese music group. In addition, the study also highlights the orchestra's contributions to the development of China's ethnic music and the ongoing musical reform in China. This information can be valuable for scholars, music enthusiasts, and cultural researchers who are interested in exploring Chinese music and culture. The objective of this study was to describe the knowledge of the Chinese National Orchestra at China's Sichuan Conservatory of Music. This study uses qualitative research and interview methods. The fieldwork method is primarily used for data collection in combination with document information. The results showed that the Chinese National Orchestra is the most prominent folk music group in China and is part of the current musical reform. It has a high reputation in China for its works and band performance level and has greatly contributed to China's ethnic music development. Its instruments include string, string plucked, blow, and percussion, which are the four main types of Chinese folk instruments. The article also highlights the importance of instrument reform in the development of Chinese national instrumental music, and the Chinese National Orchestra will continue to make contributions to the promotion of Chinese folk music.